2004
DOI: 10.1194/jlr.m300396-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-linolenic acid reduces COX-2 expression and induces apoptosis of hepatoma cells

Abstract: Although the mechanisms underlying FAS overexpression in cancer are largely unknown, recent evidence (7-10) strongly suggests that, as in liver, FAS gene transcription in tumor cells is modulated by the sterol regulatory element binding protein-1 (SREBP-1).SREBP-1 is synthesized as an integral protein of the endoplasmic reticulum membranes. As its C-terminal regulatory domain interacts with SREBP cleavage-activating protein (SCAP), the SREBP/SCAP complex migrates to the Golgi membranes, where a two-step cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 56 publications
3
45
0
1
Order By: Relevance
“…The pro-apoptotic effect of dietary n-3 PUFAs was observed also in vivo using a variety of animal models of cancer, such as rats bearing carcinogen-induced neoplastic and pre-neoplastic lesions in urothelium [151] and colon [152,153], rat tumors transplanted in syngeneic animals including 3924A Morris rat hepatocarcinoma [154,155], or tumors obtained implanting human cells in nude mice, such as human colon adenocarcinoma cells [15], thymoma cells [156], human breast cancer cells [157]. Moreover, increased apoptosis was observed also in normal splenic lymphocytes obtained from Balb/c mice treated with a fish oil diet [158].…”
Section: Other Cancer Cellsmentioning
confidence: 95%
“…The pro-apoptotic effect of dietary n-3 PUFAs was observed also in vivo using a variety of animal models of cancer, such as rats bearing carcinogen-induced neoplastic and pre-neoplastic lesions in urothelium [151] and colon [152,153], rat tumors transplanted in syngeneic animals including 3924A Morris rat hepatocarcinoma [154,155], or tumors obtained implanting human cells in nude mice, such as human colon adenocarcinoma cells [15], thymoma cells [156], human breast cancer cells [157]. Moreover, increased apoptosis was observed also in normal splenic lymphocytes obtained from Balb/c mice treated with a fish oil diet [158].…”
Section: Other Cancer Cellsmentioning
confidence: 95%
“…In hepatocarcinoma cells, n-3 PUFAs modulate the expression of CCAAT/enhancer-binding protein (C/EBP) transcription factors (18,19). C/EBPs (␣, ␤, ␦, ␥, ⑀, and ) represent a family of master regulators that play an essential role in controlling cell proliferation and differentiation processes of several cell types, including myeloid cells (20).…”
mentioning
confidence: 99%
“…29 Dai et al 30 showed that polyunsaturated fatty acids are cytotoxic to tumor cells, and of the fatty acids tested, linoleic acid (LA) and α-linolenic acid (ALA) were the most effective in suppressing the growth of normal gastric cells ( . The induction of apoptosis by α-linolenic acid (18) (ALA) was observed by Vecchini et al 31 and Scheim 32 and likely occurred because of the reduction of nitric oxide, as proposed by Deshpande et al 33 In recent studies with mouse models, ALA (18) reduced breast tumor growth while increasing the efficacy of chemotherapeutic agents. However, these studies did not confirm whether the effects were caused by ALA or its metabolites.…”
Section: Resultsmentioning
confidence: 92%